"From the outside": body and nature, fear and gender in surfing - Bandeira, Marília Martins; Rubio, Kátia (Brazilian journal of physical education and sport, 2011)
The main goal of this research is to describe the dynamics of surfing and its meanings, mainly the human/nature relation established through the sport. Meanwhile, other goals were added: discussing the approach to the field by the researcher, the possibility this researcher could investigate through her own body and the gender matter in the sport. About the main aim of the research, living and experiencing the sport itself, meaning, to the relation between the surfer and the sea, was found in the body sensations experienced through techniques such as paddling, sitting, duck diving and dropping a wave. Being able to go out is associated to a successful return to man's communion with nature, making outside's colors, shapes and sensations the privilege of whoever transposes the challenges and difficulties of becoming and being a surfer. However, these sensations are held as being only possible for courageous and agile bodies, at first, understood as male ones. Surfing as a field where the feminine is still the exception, allows the thinking that, even though nature sports and outdoor education have the potential to promote new political conducts and environmental sensitivity virtues, they are not free from reproducing other domination standards.